Yield to maturity determinants in Indonesia corporate bonds with leverage as moderating variable - Yosephine Amanda Bonowati; Pardomuan Sihombing (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The capital market is a forum for companies to sell shares and bonds in the hope of obtaining additional funds raised from the proceeds of selling part ownership of the company or issuing debt securities. The long-term market or commonly called the capital market has a variety of instruments that can be considered for investors. Furthermore, the purpose of this study is to analyze the important determinants which can have an impact on the yield to maturity of company obligations in Indonesia by placing leverage variable as a moderation variable. The data in this study was obtained from 25 company bonds as a sample of the total population of 59 corporate bonds in industrial sector which were further tested with panel data analysis techniques. It made the total data of 75 with 3 years of research duration. This study found that profitability, leverage and company size influenced the yield to maturity of company bonds in Indonesia. otherwise, bond ratings were found to have no effect. Subsequent findings suggest the role of leverage as a moderation variable. In addition, the end of this part of the study presents practical and academic advice as a form of researcher contribution, to invest in corporate bonds with higher degree of profitability, leverage and company size.